Is the perception of anxiety in dental care by children and their parents concordant? - Aline TRAVESSINI; Jéssica Copetti BARASUOL; Josiane Pezzini SOARES; Mariane CARDOSO; Michele BOLAN (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Objectives: This research evaluated the caregivers' perception on dental anxiety of their children and verified its association with independent variables: caregivers' dental anxiety and the reason for their last dental appointment, socioeconomic factors, caregivers and children's last dental visit, children's oral health status, dental anxiety and kind of dental appointment. Methods: Fifty-eight children aged 6 to 9 years old and their caregivers participated in the study. For this cross-sectional study the participants were selected from a clinical study where half of the children received fluortherapy and the other half tooth extraction. The caregivers answered questions about socioeconomic status and to evaluate their dental anxiety and the perception on children's dental anxiety they answered the Dental Anxiety Scale and Dental Anxiety Question, respectively. To evaluate children's dental anxiety the Modified Venham Picture Test was applied and their oral health status was verified with the DMFT index. Data were analyzed with Chi-square, Fisher's Exact and Mann-Whitney's test. Results: The frequency of the caregivers' perception on dental anxiety of their children were 50.9%. However, 41.4% of children reported dental anxiety. There was a significant difference between Dental Anxiety Question and Modified Venham Picture Test (p=0.002). There was no relationship between caregivers' perception on dental anxiety of their children and other independent variables. Conclusion: There was a significant difference between children's dental anxiety and the perception of it by those caregivers.